Aplicación de un dispositivo didáctico basado en el modelo holístico del pensamiento geométrico para mejorar la cognición espacial en problemas de análisis vectorial - Coello Pisco, S.; González Cañizalez, Y. (Revista Mexicana de Física E, 2018)
The procedural learning is a strategy that allows improving the skills, through the reflexive exercise in diverse techniques, skills to do concrete things. In this study we provide an overview of how to implement this learning for diagnosis and improve spatial cognition in solving vector problems. Through a methodology based on design to optimize geometric skills (visualization - design-construction-transfer), following theories of teaching - learning about levels of geometric reasoning and psychology on spatial cognition. The result of the implemented methodology showed that it is possible to improve at least one level, the geometric thinking of the students of Physics Engineering 1 of the State University of Guayaquil, according to the Van de Hiele model. Tales measurements reflected relevant facts that allowed elaborating a new instructional material to improve the academic performance of the students, through didactic techniques to improve their spatial cognitive skills.